IRAK2 directs stimulus-dependent nuclear export of inflammatory mRNAs - Zhou, Hao; Flotho, Annette; Melchior, Frauke (eLife, 2017)
The stimulation of lipopolysaccharides induced nuclear localization of IRAK2 to facilitate nuclear export of a specific subset of inflammation-related messenger RNAs for translation in murine macrophages.